The determinants of currency crises a political economy approach - Rother, Bjoern (Palgrave Macmillan, 2009)
This book explores the role of political factors in the occurrence of currency crises, using an eclectic approach that blends case studies, a rigorous theoretical discussion, and econometric analysis